Diseño de un biodigestor para el aprovechamiento del desecho lactosuero en la empresa Delilácteos San Martín. (2021)
The dairy industry, as a by-product of the cheese-making process, generates whey, which has a high content of organic matter in the form of lactose, proteins and other compounds from milk. Its uncontrolled management causes pollution problems, with serious impact on the ecosystem.